KULTUR HIPPIES DALAM KARYA DIGITAL PAINTING - OGY WISNU SUHANDHA, Drs. Syafwan, M.Si., Drs. Suib Awrus, M.Pd. (Serupa The Journal of Art Education, 2018)
The creation of this final project aims to convey the message about the characteristic factors and the form of the development popular culture through the medium of visual digital painting. This work raise the social and historical of hippies culture.The creation of the art work needs to do a variety method such as making efforts to preparation, observation, searching for information, appreciation, contempation, excavation of reference, and literature which related to the main idea, as well as to deepening the material indirictly around the environment accordance in with the problem. In the concept of creating this work, the author embodies the shape figures and the variety subjects as a form of representation the popular culture. The appearance of Hippies history and cultural development is presented in the form of ten digital paintings in Pop Art style. Among them are entitled Perkumpulan, Hope #1, Hope #2, Generasi Y, The Plastic, Hippies Local, Dominasi Musik, The Zeigest, Nomads, Tamparan Keras. Keyword : Hippies Culture, Digital Painting Art